Impact of Social Environment, Financial Education, and M-Banking Features on Impulsive Buying Behavior Among Indonesian University Students - Fadhilah, Gina; Syafina, Laylan; Anggraini, Tuti (Yayasan Sinergi Kawula Muda, 2024)
This study aims to determine the effect of social environment, financial education, and e-commerce supporting features on m-banking on impulsive buying behavior. This quantitative research uses a population of students from the Faculty of Islamic Economics and Business at UIN Sumatera Utara, employing multiple linear regression analysis with SPSS v.26. The sampling method used was purposive sampling technique using the slovin formula. The results of this study can highlight the importance of more integrated and practical financial education programs in universities. If it is proven that lack of financial literacy increases impulse buying behavior, educational institutions can develop curricula that focus more on money management and the impact of impulse spending. If m-banking features are proven to contribute to impulse buying behavior, then app developers can introduce features that encourage users to be more conscious about their spending. If peer influence is shown to have a significant impact on impulse buying behavior, then there needs to be a social intervention that educates students about social influences on their spending. Thus, collaboration between universities and m-banking service providers can strengthen financial education and impulse spending control efforts.